Effects of Employee Learning, Knowledge, and Creativity on Employee Performance in Cigarette Companies in Kudus - Dewani, Anggi Cahyaningrum; Abadi, Ferryal (International Journal of Science and Society, 2024)
Current competitive conditions are increasing and very competitive. This requires companies to be able to improve the performance of their employees in terms of increasing productivity. Competitiveness: To survive in an ever-changing market environment, companies need to utilize Human Resources (HR), especially employee performance. Employees are a key element of an organization; the success or failure of an organization depends on the performance of its employees. This research aims to determine the relationship and analyze the effect of employee learning on employee knowledge, employee creativity and employee performance, employee creativity on employee satisfaction, employee knowledge on employee performance, and employee satisfaction on employee performance. Respondents in this study were 135 respondents. The sample in this study was employee staff at a cigarette company in Kudus. This research is quantitative in nature with an analysis method using the PLS Structural Equation Model (SEM). The research results show that employee learning has a positive effect on employee knowledge, employee creativity, and employee performance, employee creativity has a positive effect on employee satisfaction, employee satisfaction has a positive effect on employee performance, and employee knowledge has a positive effect on employee performance.